Propuesta del Canon Minero como tributo extrafiscal para impulsar el desarrollo Regional de Ancash - Apaza Flores, Marco Orlando (2018)
The investigation deals with relevant aspects of mining royalties as extra fiscal tribute for Regional Development Ancash, to his knowledge propose guidelines and / or recommendations that integrate the mining canon as a separate income tax income that contributes in some way to remedy pollution caused by mining activity and generate sustainable regional development over time to the extent that its use is integrated into the economy of the town and can be perceived by the population. The main objective of the study is focused on Investigate necessary, relevant and sufficient information to demonstrate that the mining canon as extra fiscal tribute, contribute to the regional development of Ancash, which impinges positively on the level of regional development and that of the mining canon is intended to the preservation and conservation of the environment. Research has shown that indeed the doctrine and theoretical bases endorse the mining canon as a tribute extra fiscal character , to conform to characteristics of their nature, thereby sought the fee is determined independently of the income tax for in any scenario either economic profit or loss of the mining companies, the payment is made by the exploitation of a nonrenewable natural resource to be compared to the preservation and conservation of the environment and lead to an integral development of population .